How High-Frequency Users Embraced Cannabis Regulation in Uruguay. - Queirolo, Rosario; Álvarez, Eliana; Sotto, Belén; Cruz, José Miguel (Journal of Drug Issues, 2023)
How cannabis legalization affects users' behaviors? In this paper, we describe changes in the way users access cannabis in Uruguay before and after the implementation of cannabis regulation. We explore the differences between users that access through the legal, black, and gray markets. To do so, we rely on two face-to-face surveys of high-frequency users using the Respondent Driven Sample technique. The first survey was conducted at the beginning of the regulation implementation in 2014, and the second one in 2017. Results indicate that cannabis users gradually moved to the legal market, and most switched to the gray market. Furthermore, users kept acquiring cannabis from the black market even when using legal mechanisms. Considering these results, we argue that the strict regulations imposed in Uruguay may have operated as barriers for consumers to abandon the black market completely. These findings show that the specifics of each legalization policy matter.